Rehabilitation of Ganga Khadar and Khola Areas of Western Zone of U.P. by Utilizing Tall Planting Technique - Lal, Shyam (Indian Forester, 1998)
Tall planting techniques adopted for rehabilitation of Khadar and Khola areas and success of species like Dalbergia sissoo, Bombax ceiba, Holoptelia integrifolia, Pongamia pinnata, Populus spp., Terminalia arjuna, Syzygium cumini, Azadirachta indica and Acacianilotica are described in detail.